A Model For Fractured Well Performance Coupled WithComplex Seepage Mechanism in Shale Gas. Issue 3 (3rd May 2020) - Xun, Yan; Jing, Sun; Dehua, Liu
ABSTRACT: Hydraulic fracture is a key technology for high-efficiency development of shale gas, and the flow mechanism of fractured well with Stimulated Reservoir Volume (SRV) is complex in shale gas. In this paper, an apparent permeability model is proposed, which can not only reflect the multi-scale flow characteristics in shale gas but also characterize the variation of permeability with effective stress. In addition, a composite model for a fractured well with SRV is established, which comprises multiscale, geomechanics and adsorption phenomenon. The object of this paper is to investigate some important impacts on a fractured well with SRV. The results reveal that the cumulative gas production will decrease sharply when the shale gas reservoir stress-sensitive coefficient increases. Additionally, the gas production rate and cumulative gas production will increase with the increase of SRV permeability. And, the adsorption phenomenon has an influence on shale gas seepage and sorption capacity, the larger Langmuir volume, the richer adsorption gas content in shale gas. And, more adsorbed gas will be exploited into free gas, which slows down the production decline of gas wells. The production of gas well will increase with the increase of perforation thickness of gas reservoir.